Unilateral spatial neglect, global processing deficit and prosopagnosia following right hemisphere stroke： a case report - Lu, Xue-song; Ye, Jing; Zhou, Shu; Lu, Bing-xun; Chen, Xian-hong (Chinese medical journal, 2005)
Although unilateral spatial neglect, global processing deficit, or prosopagnosia followingbrain damage has been usually reported separately, to our knowledge, a report on a patient with the three mentioned syndromes has not been reported. We now present a case that developed unilateral spatial neglect, global processing deficit and prosopagnosia after right hemisphere stroke in September 2004.